The Storm Supplementary Reading Material - Hunt, Roderick (China Oxford University Press, 2012)
On a very windy and stormy day, the treehouse that Biff, Chip, Kipper, and Floppy love collapses. After school, the children$1 (Band their parents$1 (Bwork together to rebuild and repaint it. They even enjoy a cozy picnic inside the restored structure. Just when things settle, Floppy digs up a muddy golden box from the roots of the fallen tree. Inside the box, they discover an intriguing key. The story ends with Chip falling asleep, the key tucked safely in his pocket$1 (Ba magical moment hinting at future adventures.s
This short, funny tale$1 (Btypical of Level 4 stories$1 (Bis designed to support early readers by blending repetition and recognizable characters to reinforce vocabulary and comprehension. Children especially enjoy reading it multiple timess